2011
DOI: 10.1001/archgenpsychiatry.2011.80
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Neuronal Compensation During Episodic Memory in Subjective Memory Impairment

Abstract: These results suggest that SMI is accompanied by functional alterations in hippocampal integrity that reflect early neuronal dysfunction and by compensatory mechanisms that preserve memory performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
113
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(126 citation statements)
references
References 56 publications
10
113
1
2
Order By: Relevance
“…It has been suggested that memory breakdown in AD is related to a marked reduction of integrated activity within a distributed network, including hippocampus and DLPFC (Grady et al, 2001). Further support for the relevance of hippocampal-prefrontal interaction in AD risk was given by a recent study by our group, where we demonstrated that subjective memory impairment-an early, pre-MCI stage in the continuum of Alzheimer's disease manifestation-is characterized by early hippocampal dysfunction and increased compensatory effort, reflected in DLPFC activation, to enable sustained performance in the presence of early pathology (Erk et al, 2011). A recent fMRI study provided evidence for aberrant activation in the same regions, namely DLFPC and hippocampus, during working memory performance in a small sample of healthy young individuals genotyped for rs11136000 (Lancaster et al, 2011).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…It has been suggested that memory breakdown in AD is related to a marked reduction of integrated activity within a distributed network, including hippocampus and DLPFC (Grady et al, 2001). Further support for the relevance of hippocampal-prefrontal interaction in AD risk was given by a recent study by our group, where we demonstrated that subjective memory impairment-an early, pre-MCI stage in the continuum of Alzheimer's disease manifestation-is characterized by early hippocampal dysfunction and increased compensatory effort, reflected in DLPFC activation, to enable sustained performance in the presence of early pathology (Erk et al, 2011). A recent fMRI study provided evidence for aberrant activation in the same regions, namely DLFPC and hippocampus, during working memory performance in a small sample of healthy young individuals genotyped for rs11136000 (Lancaster et al, 2011).…”
Section: Discussionsupporting
confidence: 64%
“…During fMRI scanning, subjects completed three consecutive blocks of memory tasks, based on a paradigm previously used for imaging genetics, as part of a functional imaging genetics battery (Erk et al, 2010(Erk et al, , 2011. The encoding task consisted of 16 face-profession pairs and 24 head contours with four blocks of four face-profession pairs and four blocks of six head contours each.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SCC has also been found to be associated with the use of more compensatory strategies such as increased effort, cognitive strategies and use of external aids/tools (Garrett et al 2010). These reported phenomena converge with others' findings of compensatory neural activation patterns during episodic (Erk et al 2011) and working memory tasks (Sandström et al 2012) in individuals with SCC (compared to controls) even when no decrements in task performance are seen.…”
Section: Discussionsupporting
confidence: 78%
“…Recently, various neuroimaging studies on elderly participants have found SCC (even without manifest cognitive impairments) to be related to altered neuronal/ brain functioning that may be non-pathological or Erk et al 2011;Scheef et al 2012;Striepens et al 2010;Hohman et al 2011). This suggests that people may have awareness of changes in cognitive and brain functioning even when these are not detectable from conventional neuropsychological assessments.…”
Section: Discussionmentioning
confidence: 99%